2006
DOI: 10.1111/j.1365-2699.2006.01466.x
|View full text |Cite
|
Sign up to set email alerts
|

Are niche‐based species distribution models transferable in space?

Abstract: based on the area under the curve of a receiver-operating characteristic plot (ROC plot); TI, transferability index. ABSTRACTAim To assess the geographical transferability of niche-based species distribution models fitted with two modelling techniques.Location Two distinct geographical study areas in Switzerland and Austria, in the subalpine and alpine belts.Methods Generalized linear and generalized additive models (GLM and GAM) with a binomial probability distribution and a logit link were fitted for 54 plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
720
1
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 690 publications
(751 citation statements)
references
References 88 publications
27
720
1
3
Order By: Relevance
“…Despite their broad use, uncertainties about nichebased model predictions remain high (Hampe, 2004;Heikkinen et al, 2006;Randin et al, 2006). To date, the main drawback of niche-based models is their inability to consider important relationships such as biotic interactions, mortality, or growth (Davis et al, 1998;Hampe, 2004) and their reliance on observed distributions, which are the results of long-term historical factors (e.g., postglacial recolonization and human management), and environmental stochasticity, among other factors.…”
Section: Discussionmentioning
confidence: 99%
“…Despite their broad use, uncertainties about nichebased model predictions remain high (Hampe, 2004;Heikkinen et al, 2006;Randin et al, 2006). To date, the main drawback of niche-based models is their inability to consider important relationships such as biotic interactions, mortality, or growth (Davis et al, 1998;Hampe, 2004) and their reliance on observed distributions, which are the results of long-term historical factors (e.g., postglacial recolonization and human management), and environmental stochasticity, among other factors.…”
Section: Discussionmentioning
confidence: 99%
“…Such a measure must identify how well predictions fit observed data (dealing appropriately with the uncertainty in the observations themselves) while penalizing for model complexity, and should remain unaffected by both autocorrelation in the observed pattern [51] and prevalence [50]. Ideally, models should be tested against independent data, such as in an introduced range [91,92], through use of historic [93] or palaeontological [47] datasets to retrodict distribution, and through the use of simulated data where the ability of the model to recover known processes is a measure of performance.…”
Section: Discussionmentioning
confidence: 99%
“…There is currently much debate about the basic assumptions underlying this approach (e.g. Pearson & Dawson 2003;Hampe 2004;Pearson & Dawson 2004;Heikkinen et al 2006;Dormann 2007a;Beale et al 2008;Jiménez-Valverde et al 2008;Thuiller et al 2008;Araújo et al 2009;Aspinall et al 2009;Beale et al 2009;Duncan et al 2009;Morin & Thuiller 2009;Peterson et al 2009;Willis & Bhagwat 2009;Chapman 2010;Mouton et al 2010;Real et al 2010;Willis et al 2010b), namely that present-day distributions are controlled by climate (Araújo & Luoto 2007;Beale et al 2009;Blach-Overgaard et al 2010;Chapman 2010), that the distributions are in equilibrium with climate today (Svenning & Skov 2004;Araújo & Pearson 2005;Svenning & Skov 2005de Marco et al 2008;Svenning et al 2008;Normand et al 2009), that the distributional data and the climate data are reliable (Rolland 2003;Kitricos & Leriche 2010) and, in the case of montane and alpine biota, that the modern climate data are from the same altitudes as where the species being modelled actually grow (Dahl 1951(Dahl , 1998Randin et al 2006;Lundquist & Cayan 2007;Pape et al 2009;…”
Section: Basic Principles and One Or A Few Indicator Speciesmentioning
confidence: 99%